Let the Stalker Beware? Analysis of the Law of Stalking in Scotland. (October 2014) - Middlemiss, Sam
This article analyses the significance of changes to the law in Scotland dealing with stalking by outlining the previous legal position and examining the new legal rules and their impact. Stalking has been proven to be extremely harmful to the victims of the behaviour and their families, and proper legislative rules to deal with it in Scotland have been long overdue. The legislative protection required for stalking victims was introduced in 2010 and it now seems an opportune time to review the legal rules and their impact in protecting victims against stalkers in Scotland. In the process, consideration of statistical data concerning stalking prosecutions is also considered. The article also includes analysis of the legal position of stalking victims in England and Wales where new offences have recently been introduced.